The hybrid identity of micro enterprises: contrasting the perspectives of community pharmacies’ owners-managers and employees - Nunes, F. G.; Anderson J. E.; Martins, L. M.; Wiig, S. (Journal of Small Business and Enterprise Development, 2017)
Purpose - The purpose of this paper was to examine the effect of ownership of community pharmacies on the perception of organizational identity and its relationships with organizational performance. Design/methodology/approach – A survey was carried out on a sample of pharmacists working in community pharmacies in Portugal. The sample comprised 1,369 pharmacists, of whom 51% were owner-managers. Measures of pharmacies’ normative (community health oriented) and utilitarian (business oriented) identities, identity strength (clear and unifying), substantive (stockholder focused) and symbolic (society focused) performance were included. Findings – Both owners and employed pharmacists rated the normative identity of pharmacies higher than the utilitarian identity. Compared with employed pharmacists, owners perceive a lower level of utilitarian identity, the same level of normative identity, and higher levels of identity strength. Normative identity and identity strength predicted symbolic performance. Normative and utilitarian identities and identity strength predicted substantive performance. The relationship between utilitarian identity and substantive performance was significant among owner pharmacists but not among employed pharmacists. Research limitations/implications – The limitations include the use of perceptive measures and the focus on the individual level of analysis. Practical implications – In order to improve pharmacies’ performance, pharmacists who manage community pharmacies are challenged to reconcile tensions arising from the coexistence of business and community health identities and from their own agency (selfserving) and stewardship (altruistic) motives. Originality/Value – This study draws on institutional, identity, and stewardship theories to understand how pharmacists, owners and employees view the identity of community pharmacies and how identity relates to organizational performance